ANALISIS KINERJA WAKTU DAN BIAYA DENGAN METODE NILAI HASIL (EARNED VALUE METHOD) STUDY KASUS : PENINGKATAN STRUKTUR JALAN DESA SANTAN ULU KEBUPATEN KUTAI KARTANEGARA - Muhammad Ali Yusran; Benny Mochtar; Tukimun, Tukimun (Media Bina Ilmiah, 2025)
Time and cost control are crucial aspects of successful construction project management. This study aims to analyze the cost and schedule performance of the Road Structure Capacity Improvement Project in Santan Ulu Village, Kutai Kartanegara Regency using the Earned Value Method (EVM). Data were collected directly from the project and analyzed to assess performance as of the 13th week, as well as to estimate the final project cost and duration. The results indicate that the project’s cost performance was efficient, with a Cost Performance Index (CPI) greater than 1, signifying that the actual cost was lower than the earned value. In terms of schedule, the project also showed positive performance, with a Schedule Performance Index (SPI) equal to 1 up to the 13th week, indicating that the project was progressing as planned. The estimated final cost of the project (Estimate at Completion/EAC) was Rp. 2,115,004,928.56, lower than the initial budget of Rp. 4,318,631,600.41, while the estimated completion time remained consistent with the original plan of 17 weeks. These findings demonstrate that the project was managed efficiently and on schedule. The EVM method has proven effective in providing a comprehensive overview of project performance and is thus recommended as a decision-support tool in construction project management